Open-shell donor–π–acceptor conjugated metal-free dyes for dye-sensitized solar cells. Issue 9 (28th August 2020) - Sabuj, Md Abdus; Rai, Neeraj
Abstract : Open-shell dyes with small diradical character ( y < 0.10) lead to absorption in the near-infrared region. Abstract : Dye-sensitized solar cells (DSCs) have drawn a significant interest due to their low production cost, design flexibility, and the tunability of the sensitizer. However, the power conversion efficiency (PCE) of the metal-free organic dyes is limited due to the inability of the dye to absorb light in the near-infrared (NIR) region, leaving a large amount of energy unused. Herein, we have designed new DSC dyes with open-shell character, which significantly red-shifts the absorption spectra from their counterpart closed-shell structure. A small diradical character ( y < 0.10) is found to be beneficial in red-shifting the absorption maxima into the NIR region and broadening up to 2500 nm. Also, the open-shell dyes significantly reduce the singlet–triplet energy gaps (Δ E ST ), increase the total amount of charge-transfer to the semiconductor surface, reduce the exciton binding energy, and significantly increase the excited-state lifetimes compared to the closed-shell systems. However, the closed-shell dyes have higher injection efficiency with increased intramolecular charge transfer (ICT) character. Our study reveals the design rule for open-shell DSC dyes to be able to absorb photons in the NIR region, which can increase the efficiency of the solar cell device.